Studying principals' resource allocation and affecting resource factors for physical education in Finland - Rämä, Markus (2013)
The aims of the present study were to investigate principals’ opinions of PE resourcing in schools. Resourcing was divided for different resourcing factors in schools: principals’ money allocation, qualified PE teachers, PE teachers’ in-service education, extracurricular PE and optional PE courses. These resource factors were investigated by associations between school size and different resourcing factors and between school’s regional location and different resourcing factors. Other aims were to study if principals’ and PE teachers’ opinions of PE resourcing diverge and to compare results of PE resourcing to previous PE evaluations study (Huisman 2004) in 2003.